Growth and maintenance costs of leaves and roots in two populations of Quercus ilex native to distinct substrates - Laureano, Raquel G.; García-Nogales, Ana; Seco, José I.; Rodríguez, Jesús G. P.; Linares, Juan C.; Martínez, Feliciano; Merino, José (Plant and Soil, 2012)
Aims This work tests the hypothesis that growth and maintenance costs of plant organs are higher in more stressful soils. Methods Two populations of Quercus ilex L were selected in the southern Iberian Peninsula, these growing in similar climates but different soil types, namely a brown well-developed soil on slate rock, and a stressful lithosol on gypsum rock. In both localities, growth and maintenance respiration were measured in undetached young and mature leaves (trees under natural conditions) and fine roots (hydroponically grown seedling). Results Young leaves of the two populations displayed an almost identical growth cost (1.53 g glucose g -1 ). The maintenance cost was higher in the young (40.2 vs. 25.3 mg glucose g -1 day -1 ; P<0.05) and in the mature (7.64 vs. 4.33 mg glucose g -1 day -1 ; P<0.001) leaves of individuals growing in gypsum soils. The growth cost of fine roots was the same in both populations (1.18 g glucose g -1 ) while the maintenance cost was higher in the Gypsum population (8.95 vs. 7.39 mg glucose g -1 day -1 ; P<0.01). Conclusions The results show for first time that the cost of organ maintenance may be related to the degree of soil stress in their native habitats.
Keywords: ecotypes; evergreen leaves; growth respiration; maintenance respiration; mediterranean species; root respiration; sclerophylly; soil stress

The cost of stress resistance: construction and maintenance costs of leaves and roots in two populations of Quercus ilex (Tree Physiology, 2008)
We tested whether growth and maintenance costs of plant organs vary with environmental stress. Quercus ilex L. seedlings from acorns collected from natural populations in the northern Iberian Peninsula and in a lower elevation and putatively less stressful habitat in the southern Iberian Peninsula were grown in pots under the same conditions. Growth and maintenance respiration were measured by CO2 exchange. Young leaves from 5-month-old seedlings of both populations had similar mean specific leaf areas, nitrogen and carbon concentrations and specific growth rates, and almost identical growth costs (1.26 g glucose g−1). Leaf maintenance cost was higher in northern than in the southern population (27.3 versus 22.4 mg glucose g−1 day−1, P < 0.01). In both populations, leaf maintenance cost decreased by 90% as leaves aged, but even in mature leaves, the maintenance cost was higher in the northern population than in the southern population (3.38 versus 2.53 mg glucose g−1 day−1, P < 0.01). The growth costs of fine roots < 1 mm in diameter were similar in the two populations (1.20 g glucose g−1), whereas fine root maintenance cost was higher in the northern population than in the southern population (9.86 versus 7.45 mg glucose g−1 day−1; P < 0.05). The results suggest that the cost of organ maintenance is related to the severity of environmental stress in the native habitat. Because the observed differences in both leaves and roots were constitutive, the two populations may be considered ecotypes.
10.1093/treephys/28.11.1721